(untitled) (International Journal of Environmental Sciences, 2025)
Phytopathogens including fungi, bacteria, viruses, and oomycetes are major contributors to global agricultural losses, threatening food security and economic sustainability. Conventional chemical pesticides, while effective, pose serious environmental and health risks, and their overuse has led to the development of resistant pathogen strains. In response to these challenges, essential oils (EOs), derived from aromatic plants, have emerged as promising biocontrol agents due to their potent antimicrobial properties, biodegradability, and compatibility with integrated pest management (IPM) systems. This review presents a comprehensive examination of the role of essential oils in controlling phytopathogens. It explores their botanical origins, bioactive chemical constituents (such as thymol, eugenol, carvacrol, and citronellal), and common extraction methods including hydrodistillation and cold pressing. The paper delves into their mechanisms of action, which include disruption of microbial membranes, inhibition of spore germination and mycelial growth, interference with quorum sensing in bacteria, and antiviral or ant oomycete effects. The synergistic potential of EOs with other natural agents is also discussed. A critical assessment of experimental findings from both in vitro and in vivo studies highlights the efficacy of specific EOs—such as those from Melaleuca alternifolia, Thymus vulgaris, Origanum vulgare, Syzygium aromaticum, and Cymbopogon citratus against major plant pathogens. However, the review also identifies key limitations, including variability in EO composition, lack of field validation, scalability issues, and regulatory constraints.